2007
DOI: 10.4028/www.scientific.net/msf.561-565.2179
|View full text |Cite
|
Sign up to set email alerts
|

High Cycle Fatigue Behavior of Thermally Oxidized Ti6Al4V Alloy

Abstract: In this study, the effect of thermal oxidation on the high cycle rotating bending fatigue behavior of Ti6Al4V alloy was investigated. Oxidation, which was performed at 600°C for 60 h in air, considerably improved the surface hardness and particularly the yield strength of the alloy without scarifying the tensile ductility. Unfortunately, the rotating bending fatigue strength at 5x106 cycles decreased from about 610 MPa to about 400 MPa upon oxidation. Thus, thermal oxidation leaded a reduction in the fatigue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Leinenbach and Eifler [30], who studied the fatigue behavior of Ti6Al7Nb alloy in an oxygen-saturated Ringer's solution, reported a loss in fatigue strength after TO conducted in air at 675°C for 3 h. For the examined Ti6Al7Nb alloy the applied TO process led to some reduction in fatigue strength (about 10 % compared to the UT state) without considerable change in the tensile properties [31]. It should be noted that the TO process parameters of the present study caused severe reduction in the fatigue strength of the Ti6Al4V alloy (about 34 % compared to the UT state) owing to the formation of a relatively rougher and thicker OL [32].…”
Section: Wear Testsmentioning
confidence: 87%
“…Leinenbach and Eifler [30], who studied the fatigue behavior of Ti6Al7Nb alloy in an oxygen-saturated Ringer's solution, reported a loss in fatigue strength after TO conducted in air at 675°C for 3 h. For the examined Ti6Al7Nb alloy the applied TO process led to some reduction in fatigue strength (about 10 % compared to the UT state) without considerable change in the tensile properties [31]. It should be noted that the TO process parameters of the present study caused severe reduction in the fatigue strength of the Ti6Al4V alloy (about 34 % compared to the UT state) owing to the formation of a relatively rougher and thicker OL [32].…”
Section: Wear Testsmentioning
confidence: 87%
“…Further dissolution of oxygen in titanium renders α-Ti stable and β-Ti disappears. Thermal oxidation (TO), which is based on diffusion of oxygen atoms into titanium and its alloys at high temperatures in any oxygen containing ambient, produces a graded surface consisting of titanium oxide as the compound layer and an oxygen enriched α-Ti solid solution as the diffusion zone (DZ) [6][7][8]16,[19][20][21][22][23][24][25][26]. A cross -sectional optical micrograph of the TO treated Ti6Al4V alloy is presented in Fig.…”
Section: Thermal Oxidationmentioning
confidence: 99%
“…For instance, the fatigue limit of Ti-6Al-4V and Ti-6Al-7Nb was reduced by 30 and 10% respectively after 600°C/60 h CCT in air (Meydanoglu et al, 2008). Cingi et al (2007) reported that the rotating bending fatigue strength of Ti-6Al-4V alloy at 5 ¥ 10 6 cycles decreased from 610 to 400 MPa (i.e. a 34% reduction) following 600°C/60 h CCT in air.…”
Section: Fatigue and Fretting Fatigue Propertiesmentioning
confidence: 97%